ALPHA GENERATION'S ENTHUSIASM FOR RECITING THE KORAN IN THE ERA OF REVOLUTION 4.0 (CASE STUDY OF THE COMMUNITY OF CIBEBER VILLAGE, KIARAPEDES, PURWAKARTA) - Selvia Ru'yatus Saefullah; Neng Puja Nurmalasari; T iwi Helawati; Hida Dzalillah (International Journal of Social Science, 2023)
The era of revolution 4.0 brings positive and negative influences in the world of education. One of the negative impacts is cases of gadget addiction in children, both young children and teenagers. The rise in cases of gadget addiction in the world, especially in Indonesia, has a bad influence on students. Most students in Indonesia, especially in rural areas, when they reach the age of 12, stop reciting the Koran, but things are different in one of the villages in Purwakarta Regency, Kiarapedes District, namely Cibeber Village, in the village These alpha generation children are still very enthusiastic about taking part in the recitation, this is an attraction for researchers to find out what factors make the alpha generation in Cibeber Village very enthusiastic about taking part in the recitation. This research uses a qualitative approach by collecting primary data using interviews with alpha generation children, parents and Koran Koran teachers in Cibeber Village, Kiarapedes District, Purwakarta Regency. The results of the research show that the alpha generation's enthusiasm for reciting the Koran in Cibeber Village occurs because of motivation from teachers, friends, themselves, and parents as well as because of the existence of a healthy environment and the underlying factors that the alpha generation in Cibeber Village is not addicted to gadgets because there are several areas in the village. Cibeber has an unstable signal and busy activities starting from formal schools, religious schools and continuing with recitations